Perceptions of safety, subjective effects, and beliefs about the clinical utility of lysergic acid diethylamide in healthy participants within a novel intervention paradigm: Qualitative results from a proof-of-concept study. (March 2022) - Hendricks, Peter S; Copes, Heith; Family, Neiloufar; Williams, Luke TJ; Luke, David; Raz, Shlomi
Background: Classic psychedelics show promise in the treatment of mental health conditions; however, more scalable intervention protocols are needed to maximize access to these novel therapeutics. In this proof-of-concept study, perceptions of safety, subjective effects, and beliefs about the clinical utility of lysergic acid diethylamide (LSD) were evaluated among healthy participants ( N = 31) administered 50 to 100 µg LSD in a treatment paradigm conceptualized as more scalable than traditional approaches to administering classic psychedelics. Methods: Semi-structured interviews assessed participants' expectations, experience, and thoughts on the safety and efficacy of the study design. These interviews were transcribed for thematic analysis relating to perceptions of safety, subjective effects, and beliefs about the clinical utility of LSD. Results: Most participants felt safe throughout the study, with a minority reporting concerns related to having a challenging experience that diminished over time. Participants attributed their feelings of safety to the study structure and support of their attendants, which allowed them to "let go" and immerse themselves in the experience without pre-occupation. Furthermore, participants reported transcendent, mystical-type experiences characteristic of classic psychedelics, with almost half highlighting the prominent role played by music during the acute period of drug action. Finally, participants endorsed support for the clinical utility of LSD in controlled environments, expressing the belief that LSD is safe and has the potential to help others. Conclusion: Findings provide preliminary support for the feasibility of this scalable interventional paradigm and set the stage for future critical research with clinical populations.